A study on implementation of human-friendly system for providing safety management in IOT environment - Sang Kim, Young; Chan Kim, Hye (International Journal of Engineering and Technology, 2018)
This paper suggests the Human-friendly integrated system on the basis of IoT, which can prevent a Haenyeo at work under the sea from an unexpected accident. This system can process thedata based on the stored data, after building the database of the information from Smart Taewak. As a united software, IoT based Haenyeo Safely Managing Software (IOTHSMS) is composed of Data Collection Module, Server Device, Emergency Alarm Module, and Monitoring Program, providing service in various ways. Smart Swimming Goggles collect the information on Haenyeoâ€™s activities and gives it to Smart Taewak, which transmits the data to IoTHSMS server. IOTHSMS needs to access to a PC or a Mobile Phone. IOTHSMS divides the information into the location and the condition of Haenyeo to indicate the POSITION information of Haenyeo at work and services provided by privileged permission. The STATE information of Haenyeo is separated into recent information and statistic one. IOTHSMS should not only have a function to manage userâ€™s information but also the authority to modify PIN number, telephone number, mobile phone number, affiliated fishing village fraternities, and emergency call number in specifically. This study improves the former goggles and Taewak as Smart goggles and Smart Taewak with an IoT technology, the device to understand and analyze the state and the location information of a Haenyeo every real time by measuring her body condition and diving information.Â